The Nature and Determinants of Capital Structure in Indian Service Firms - Jagannathan, Uday Kumar; Suresh, N. (Indian Journal of Finance, 2017)
In the Indian context, the service sector has played an important role in the development of the economy since reforms in 1991, and is expected to continue to contribute significantly to the growth in the economy in the coming decades. With this rationale, service firms were selected for the study for the time frame from 2011 to 2015, and the nature and determinants of their capital structure are studied. Since interest expense gives tax shelter to firms, the trade-off theory suggests that firms may be incentivized to use these shelters and thus increase leverage. Therefore, this theory was putÂ to test here. The pecking order theory which states that the firm will raise capital from internal accruals followed by debt and finally equity was supported by the research in this paper. Further conclusion derived from the study was that capital structure, as measured by debt-to-asset ratio, remained stable in the 5- year period with an industry average of about 0.31. This study also tested the hypothesis on the trade off model of capital structure, which stated that there is an optimal capital structure which firms tend to move toward, and several approaches were adopted to measure if this hypothesis was true. While firms’ debt level in a year could be reasonably predicted by the debt-to-asset ratio in the prior year, the fit of the OLS regression became progressively worse as the number of lagging years was increased, suggesting that capital structure was sticky. The industry debt-to-asset ratio, while statistically significant as a predictor of firm debt level, resulted in a regression with a poor overall fit. While there is evidence to accept the pecking order hypothesis, there was not enough evidence to reject the trade-off model of capital structure for Indian service firms in the selected time period.